Mechanism and Control of Cable Breakage in a Roadway with Thick Top Coal in a Rockburst Mine - Ying Xu; Xiekang Zhou; Weimei Gong (Advances in Civil Engineering)
Because top coal is not stable, a roadway with thick top coal often appears to mine pressure problems, such as bolt failure, cable breakage, and roof caving. In particular, these problems are more serious in rockburst mines. Based on a cable breakage case of No. 3 roadway in Xingcun coal mine, the paper analyzed the stress and elastic energy evolution law of surrounding rock and stress state of cable in the 3# roadway by means of the numerical simulation method. Thus, the cable breakage mechanism of the roadway with thick top coal in rockburst mine was revealed. Then, because surrounding rock grouting can reduce the stress concentration of surrounding rock and cable, surrounding rock grouting technology was proposed as control technology of cable breakage. Finally, parameters of surrounding rock grouting were designed and applied in the No. 3 roadway. The field results showed that surrounding rock grouting technology can be one of the solutions for cable breakage of roadway with thick top coal in rockburst mine. The research results of this paper can provide certain theoretical and practical value for mine pressure control of roadway.